Taller de Biodanza INFANTIL para desarrollar la capacidad de autorregulación emocional en los estudiantes de Educación Primaria, Trujillo 2019 - Avila Ruiz, Ghilda Jhoselyn (2021)
The research entitled, "INFANTIL" Biodanza Workshop to develop the capacity of emotional self-regulation in primary school students, Trujillo 2019, had the purpose of determining the impact of the same on the capacity of emotional self-regulation in the students and institution indicated above. A quasi-experimental design was used, with two groups: experimental control group with a sample of 40 students for the experimental group and 31 for the control. The results obtained after working in 15 learning sessions indicate that the aforementioned workshop has had an impact of 21.5% of effectiveness when comparing the post-test with the pre-test of the experimental group, in the process of contrasting the general hypothesis a p = 0.000 < 0.05 is observed, which shows that there is statistical significance and therefore the alternative hypothesis is accepted.